Global research prospects and trends in TFH cells and tumors: a bibliometric analysis - Lei, Hao; Hu, Jin; Zhu, Junpeng; Li, Runze; Zhao, Yu; Zhao, Yaqi; He, Guisheng; Song, Tao; Lu, Chong; Zheng, Wuping; Li, Lei; Liu, Chunping; et al. (Frontiers in Oncology, 2025)
BackgroundT follicular helper (TFH) cells, a subset of CD4+Th cells, play a critical role in B cell activation, proliferation, and differentiation primarily within B follicles in secondary lymphoid organs, essential processes for effective antibody responses. TFH cells are also implicated in various conditions, including autoimmune diseases, cancer, infectious diseases, allergies, and vaccine reactions. Despite their broad impact, a review of the literature on TFH cells and tumors has not been conducted. We aimed to fill this gap by providing a detailed analysis of the research landscape concerning TFH cells and tumors.MethodWe conducted a bibliometric analysis of literature on TFH cells and tumors from 2012 to 2024 using the Web of Science Core Collection (WoSCC). For an analysis of the global research landscape, we employed VOSviewer (version 1.6.20), CiteSpace 6.2.R6 software, and the “bibliometric” package in R language (version 4.3.2) to evaluate data on countries/regions, authors and cited authors, institutions, journals, references, and keywords. We also conducted a systematic review to summarize the global research trends, prospects, and hotspots in this field.ResultsOur analysis included contributions from 60 countries/regions, 7,864 authors, 35,853 cited authors, 1,756 institutions, 385 academic journals, 50883 references, 222 keywords, and 1,181published papers. Over the past decade, the volume of research on TFH cells and tumors had consistently increased. China published the most papers, more than double that of the United States. The top 2 authors ranked by publication volume were Gaulard, Philippe (14 articles, 379 citations), and De leval, Laurence (12 articles, 236 citations) Notably, 9 of the top 10 most published institutions were from China. Frontiers in Immunology and Immunity were the leading journals in publications and citations. A cluster analysis revealed a shift in research focus from “expression”,”B cells” and “survival” to “tumor microenvironment”, “tumor infiltrating immune cells” and “immune infiltration” in recent years.ConclusionThis bibliometric analysis suggests that TFH cells hold significant research value and potential clinical applications in tumor immunotherapy. Moreover, the bibliometric analysis offers valuable references and guidance for related research endeavors. It also points out the prevailing issues and challenges in TFH cell research, and underscores the need for further basic and clinical research to advance the related fields.